Symptoms of Fern Distortion Syndrome Resulting from Inoculation with Opportunistic Endophytic Fluorescent Pseudomonas spp - Kloepper, Joseph W.; McInroy, John A.; Liu, Ke; Hu, Chia-Hui (PloS one, 2013)
Fern Distortion Syndrome (FDS) is a serious disease of Leatherleaf fern (Rumohra adiantiformis). The main symptom of FDS is distortion of fronds, making them unmarketable. Additional symptoms include stunting, irregular sporulation, decreased rhizome diameter, and internal discoloration of rhizomes. We previously reported an association of symptoms with increased endophytic rhizome populations of fluorescent pseudomonads (FPs). The aim of the current study was to determine if FPs from ferns in Costa Rica with typical FDS symptoms would recreate symptoms of FDS. Greenhouse tests were conducted over a 29-month period. Micro-propagated ferns derived from tissue culture were first grown one year to produce rhizomes. Then, using an 8×9 randomized complete block experimental design, 8 replicate rhizomes were inoculated by dipping into 9 different treatments before planting. Treatments included water without bacteria (control), and four different groups of FPs, each at a two concentrations. The four groups of FPs included one group from healthy ferns without symptoms (another control treatment), two groups isolated from inside rhizomes of symptomatic ferns, and one group isolated from inside roots of symptomatic ferns. Symptoms were assessed 12 and 17 months later, and populations of FPs inside newly formed rhizomes were determined after 17 months. Results showed that inoculation with mixtures of FPs from ferns with FDS symptoms, but not from healthy ferns, recreated the primary symptom of frond deformities and also the secondary symptoms of irregular sporulation, decreased rhizome diameter, and internal discoloration of rhizomes. These results suggest a model of causation of FDS in which symptoms result from latent infections by multiple species of opportunistic endophytic bacteria containing virulence genes that are expressed when populations inside the plant reach a minimum level.